Environmental factors and the entrepreneurial intentions of UiTM hospitality students / Nur Azah Farhana Mohamed Fadzil ... [et al.] - Mohamed Fadzil, Nur Azah Farhana; Mohd Fuza, Zatul Iffah; Wan Kamarudin, Wan Nor Bayah; Nik Mohd Fahmi, Nik Mohammad Zulfadli (Faculty of Business and Management, 2022)
Entrepreneurship is critical in all countries, including Malaysia, in order to contribute to economic growth, job creation, and technological advancements. As a result, entrepreneurship studies are critically a phenomenon among scholars as it is considered as one of the strategies to boost the economy and enhance job creation. However, environmental factors are always vulnerable and empirically significant in influencing human behaviour. Therefore, this study aims to determine the impact of environmental factors on the entrepreneurial intention among hotel and tourism management students in UiTM Malaysia. The study investigated the impact of environment factors that focused on students' opportunity recognition and social worthiness on entrepreneurial intention among UiTM hospitality students. A cross-sectional research design was used, with a quantitative questionnaire approach. To select 217 participants, the study used probability sampling with a simple random sample technique. The model was tested using the Statistical Package for the Social Sciences, IBM SPSS Statistics 26.0. The data was then analysed using a multiple regression analysis technique. According to the findings of the study, opportunity recognition and social worthiness are significantly related to entrepreneurial intention among UiTM hospitality students.